RANCANG BANGUN APLIKASI PEMESANAN PERCETAKAN BERBASIS WEB PADA PT. SUMBER REZEKI - Yani, Achmad; Ali, Toni Saidun; Miswanto, Miswanto; Quiko, Alfonso Sabatani; Santoso, Imam (Yayasan Bina Internusa Mabarindo, 2024)
Sumber Rezeki Printing is a business entity that operates in the digital printing sector, which does setting and printing. For the Sumber Rezeki Printing transaction system, customers come with raw files and then go home with the printed results. However, the transaction system at Sumber Rezeki Printing is still carried out manually, such as in the process of creating order forms and SPK (work orders), which makes this system inefficient, especially in terms of materials and time. Based on the problems described, the author intends to create a web-based application to overcome existing problems. Therefore, the topic that will be created is